Endothelial protective activity of boldine in animal models of hypertension and diabetes mellitus / Lau Yeh Siang - Lau, Yeh Siang (2013)

(untitled)
Free radical-induced oxidative stress is involved in the pathogenesis of a number of human diseases such as diabetes mellitus, hypertension and atherosclerosis. Endothelial dysfunction, usually assessed as decreased endothelium-dependent vasodilation, precedes clinically before obvious vascular pathologies and together with oxidative stress are major predictors of disease progression. Such endothelial dysfunction is observed early in the development of the pathology and is due, at least in part, to an excessive vascular formation of reactive oxygen species (ROS) in particular superoxide anion (O2−), which reduce nitric oxide (NO) bioavailability. Epidemiological and clinical studies have demonstrated that a growing list of natural products, as components of the daily diet or phytomedical preparations are a rich source of antioxidants and may improve vascular function by enhancing NO bioavailability. In our preliminary studies, the crude extract of Phoebe grandis demonstrated significant protection of the endothelial cells against oxidative stress induced by the pro-oxidant β-NADH. Boldine ((S)-2,9-dihydroxy-1,10-dimethoxy-aporphine), the major compound in Phoebe grandis, exhibited the highest antioxidant activity, and thus, selected for further studies in animal models of hypertension and diabetes mellitus. Spontaneously hypertensive rats (SHRs) and type 1 (streptozotocin-induced) diabetic rats were treated intraperitoneally either with vehicle or boldine (20 mg/kg) for 7 days while type 2 (db/db mice) diabetic mice were treated orally to investigate the chronic effects of boldine on vascular and endothelial functions. Repeated treatment with boldine significantly improved acetylcholine (ACh)-induced endothelium-dependent relaxation in isolated SHR aortas whilst sodium nitroprusside (SNP)-induced endothelium-independent relaxations remained unaltered. Furthermore, boldine Abstract iv treatment lowered aortic O2− and peroxynitrite (ONOO−) productions and down-regulated the protein expression of the p47phox subunit of pro-oxidant enzyme nicotinamide adenine dinucleotide phosphate (NADPH) oxidase in the SHR aortas. This endothelial protective effect of boldine in hypertensive animals was achieved, at least in part, through the inhibition of NADPH-mediated O2− production. Similarly, repeated treatment with boldine significantly improved the ACh-induced endothelium-dependent relaxation of the aorta in both type 1 and 2 diabetic animals but had no effect on endothelium-independent relaxations to SNP. In addition, boldine treatment effectively reduced the hyperglycaemia-induced oxidative stress level in the vascular wall of the diabetic rats and mice. This protective effect of boldine was further confirmed in primary rat/mouse aortic endothelial cells exposed to high glucose levels. In rat aortas, this endothelial protective role of boldine were correlated with increased NO levels and reduction of vascular ROS via inhibition of the NADPH oxidase subunits, p47phox and NOX2. In the db/db mouse type 2 diabetic model, repeated treatment with boldine normalized the overproduction of ROS, and this was associated with the restored level of eNOS phosphorylation and down-regulation of protein expression of angiotensin type 1 receptor (AT1R) and oxidative stress markers (bone morphogenetic protein-4 and nitrotyrosine). Treatment with boldine, slightly decreased blood glucose levels in the type 1 diabetic rat but did not have a significant effect in the type 2 diabetic mice, Taken together, it appears that boldine may exert positive effects on the endothelium via several mechanisms including mainly by protecting NO from degradation via inhibiting the excessive production and scavenging of O2−, and additionally by increasing NO bioavailability by upregulating activity of eNOS. The present study supports a complimentary therapeutic role of a natural product, boldine in improving endothelial dysfunction associated with hypertension and diabetes mellitus by interfering with the oxidative stress-mediated signalling pathway.